2014
DOI: 10.1111/echo.12509
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Three‐Dimensional Imaging and Pressure Recovery on Echocardiographic Evaluation of Severe Aortic Stenosis: A Pilot Study

Abstract: Three-dimensional TEE is more accurate than 2DTTE and 2DTEE for determining LVOT and AA dimensions. When AS severity is determined by 3DTEE and corrected for PR using the 3D values, it needs to be reclassified from severe to moderate in almost a third of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…The concept of elliptical LVOT demonstrated to have clinical implications in aortic valve stenosis evaluation, performed either with 3D echocardiography or CT or MR imaging. In fact, the aortic valve area calculated accounting for LVOT ellipticity was closer to the area calculated at catheterization and would reclassify severe aortic stenosis as moderate . In the setting of TAVR with Edwards‐Sapien valve, Ng and coworkers demonstrated both at multislice CT and transesophageal 3D echocardiography (3D TEE) that TAVR preserved, although slightly reduced, the ellipticity index of LVOT, which was in the same order of magnitude as in our study (1.20 by CT, 1.19 by 3DTEE).…”
Section: Discussionsupporting
confidence: 80%
“…The concept of elliptical LVOT demonstrated to have clinical implications in aortic valve stenosis evaluation, performed either with 3D echocardiography or CT or MR imaging. In fact, the aortic valve area calculated accounting for LVOT ellipticity was closer to the area calculated at catheterization and would reclassify severe aortic stenosis as moderate . In the setting of TAVR with Edwards‐Sapien valve, Ng and coworkers demonstrated both at multislice CT and transesophageal 3D echocardiography (3D TEE) that TAVR preserved, although slightly reduced, the ellipticity index of LVOT, which was in the same order of magnitude as in our study (1.20 by CT, 1.19 by 3DTEE).…”
Section: Discussionsupporting
confidence: 80%
“…This is done by obtaining the LVOT diameter (D1) from the parasternal long‐axis view as measured from the inner edge to the inner edge within 0.3–1 cm below the aortic valve annulus and then applying the formula LVOT Area = π ( D /2) 2 , assuming a circular shape of the LVOT. However, 3D imaging techniques have shown that this shape is often elliptical, and only rarely circular . This leads to underestimation of LVOT area, and hence of AVA, by the CE.…”
Section: Introductionmentioning
confidence: 99%
“…When ELI is not consistent with AVAI, other modalities should be used for severity assessment. Not only TTE but also TEE can be used to define ELI . ELI has been also shown to predict outcomes after AVR, and transcutaneous aortic valve replacement (TAVR) .…”
Section: Discrepancies In Echocardiographic Measurements Of Aortic Stmentioning
confidence: 99%